2012
DOI: 10.1177/1098612x12469523
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic appearance of adrenal glands in healthy and sick cats

Abstract: The first part of the study aimed to describe prospectively the ultrasonographic features of the adrenal glands in 94 healthy cats and 51 chronically sick cats. It confirmed the feasibility of ultrasonography of adrenal glands in healthy and chronically sick cats, which were not statistically different. The typical hypoechoic appearance of the gland surrounded by hyperechoic fat made it recognisable. A sagittal plane of the gland, not in line with the aorta, may be necessary to obtain the largest adrenal measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(77 citation statements)
references
References 37 publications
(67 reference statements)
5
71
1
Order By: Relevance
“…Although adrenal disorders can be diagnosed by ultrasonography in both humans and pet animals, [10][11][12][13][14][15][16][17][18] sonographic assessment of the normal or pathologic adrenal gland of lemurs has not been reported. In this study, the anatomic, histologic, and sonographic aspects of the adrenal glands of normal lemurs (E. fulvus) are presented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although adrenal disorders can be diagnosed by ultrasonography in both humans and pet animals, [10][11][12][13][14][15][16][17][18] sonographic assessment of the normal or pathologic adrenal gland of lemurs has not been reported. In this study, the anatomic, histologic, and sonographic aspects of the adrenal glands of normal lemurs (E. fulvus) are presented.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal gland is a key organ in the adaptation of non‐human primates to stress and can become hyperplastic in monkeys chronically subjected to stress factors . Although ultrasonography proved to be effective in the diagnosis of various adrenal diseases in human studies as well as adrenal enlargement associated with hyperaldosteronism or hyperadrenocorticism in pet studies, there has been no work using ultrasound imaging to detect adrenal changes in non‐human primates affected by hormonal imbalances. According to Souza et al., this lack of literature would be due to an underdiagnosis of adrenal disorders in monkeys because ultrasonographic reference metrics of the adrenal glands are not available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adrenal glands were imaged according to a previously described protocol (Zimmer et al, 2000;Combes et al, 2013). The maximum length (craniocaudal, L) and the height of the cranial (crH) and caudal (cdH) poles (dorso-ventral) were measured on a sagittal scan of each adrenal gland.…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Combes et al (2012), the adrenal glands of hyperthyroid cats showed similar or mildly enlarged measurements with mean measurement differences of 1.6-1.7 mm in length and 0.8-0.9 mm in height. In cats with hyperaldosteronism secondary to an adrenal carcinoma, the adrenal mass has been reported as at least twice the normal adrenal size on ultrasound, or more than 10 and 3 mm difference in length and height measurements, respectively (Combes et al, 2013).…”
Section: P-valuementioning
confidence: 99%